Infrared Temperature Law and Deformation Monitoring of Layered Bedding Rock Slope under Static Load. (21st December 2020) - Tao, Zhigang; Liu, Kuiming; Cui, Xuebin; Qiao, Xiaobing; Sun, Xiaoming
Abstract : China is a mountainous and hilly country with frequent large-scale landslides with complicated mechanisms and serious damage. The layered rock slopes have the worst stability, undergo the most serious damage, and have been rarely investigated due to limitations of measurement methods and instruments. Taking the Nanfen open-pit iron mine as an example, a physical large-model similarity ratio test system is used to simulate the landslide remote monitoring process. The development of the sliding surface, stress-strain characteristics, and infrared law of the bedded rock slope are analyzed. Results show that the anchor cable with constant resistance and large deformation plays a significant role in the stability of the slope, and its maximum slip force is 420 N and 630 N, respectively. Slip and crack are the main mechanisms of energy release in layered rock slope. Some scheme improvement measures for this kind of test are put forward, which provides basis and optimization scheme for the subsequent study of layered rock slope.